Introduction to Modern Optics (2nd Edition) - Fowles, Grant R (Dover Publications, 1975)
This book is a complete basic undergraduate-level course in modern optics for students in physics, technology and engineering. The first half deals with classical physical optics; the second, the quantum nature of light. Many applications of the laser to optics are integrated throughout the text. The book includes problems and answers and 170 illustrations.